Segmentation of Portuguese customers’ expectations from fitness programs - Rodrigues, Ricardo (2018)
Expectations towards fitness exercises are the major factor in customer satisfaction in the service sector in question. The purpose of this study is to present a segmentation framework for fitness customers, based on their individual expectations. The survey was designed and validated to evaluate individual expectations towards exercises. The study included a randomly recruited sample of 723 subjects (53% males; 47% females; 42.1±19.7 years). Factor analysis and cluster analysis with Ward’s cluster method with squared Euclidean distance were used to analyse the data obtained. Four components were extracted (performance, enjoyment, beauty and health) explaining 68.7% of the total variance and three distinct segments were found: Exercise Lovers (n=312), Disinterested (n=161) and Beauty Seekers (n=250). All the factors identified have a significant contribution to differentiate the clusters, the first and third clusters being most similar. The segmentation framework obtained based on customer expectations allows better understanding of customers’ profiles, thus helping the fitness industry develop services more suitable for each type of customers. A follow-up study was conducted 5 years later and the results concur with the initial study.